Pillangósvirágú növények magtermesztésének növényvédelmi tapasztalatai ökológiai termesztésre átállt gazdaságban - Szabó, Béla; Kosztyuné Krajnyák, Edit; Szabó, Miklós; Csabai , Judit; Tóth, Csilla; Varga, Csaba (GEORGIKON FOR AGRICULTURE, 2020)
Plant nitrogen nutrition is the key issue of organic plant growing. This issue is more crucial in soils of low nutrient-supplying power and of unfavour water management properties. Growing of papilionaceous plants means the most economic alternative to grain crops. Seed prodution of hairy vetch (Vicia villosa Roth) and lupine (Lupinus albus L.) runs back over many hundred years in our region. Sowing seed of papilionaceous plants from organic production has became a commodity in great demand. Therefore, growing of hairy vetch and lupine has not only nutrient supply advance but could be profitable. Since 2015 Training Farm of University of Nyíregyháza has been carrying organic farming in 140 hectares. These two plant have a dominant role in our crop rotation. In this paper we represent our 3-year cropping experience focusing on plant protection.
Keywords: hairy vetch; lupine; organic farming